Endovascular Plug for Endobronchial Management of an Expectorated Pulmonary Artery Embolization Coil: A Case Report. Issue 2 (10th February 2023) - Crawford, Jesse M.; Patel, Priya P.; DuCoffe, Aaron R.; Tsai, Michael; Hodgson, John A.
Abstract : Pulmonary artery aneurysms are frequently managed with endovascular embolization. Rare but serious complications of coil embolization are erosion and migration of the coils into the adjacent airways, posing a risk for massive hemoptysis. We report the case of a medically complex patient with a left main pulmonary artery aneurysm treated with coil embolization who ultimately experienced transbronchial migration and expectoration of the coil. We discuss the challenging anesthetic and surgical management of these serious complications, including the use of an endovascular plug to occlude the erosion site and distal airways.